What's best for women: Gender based taxation, wage subsidies or basic income? - Ugo Colombino; Edlira Narazani (Institute for the Study of Labor (IZA), 2012)
We use a microeconometric model of household labour supply in order to evaluate, with Italian data, the behavioural and welfare effects of gender based taxation (GBT) as compared to other policies based on different optimal taxation principles. The comparison is interesting because GBT, although technically correct, might face implementation difficulties not shared by other policies that in turn might produce comparable benefits. The simulation procedure accounts for the constraints implied by fiscal neutrality and market equilibrium. Our results support to some extent the expectations of GBT's proponents. However it is not an unquestionable success. GBT induces a modest increase of women's employment, but similar effects can be attained by universal subsidies on low wages. When the policies are evaluated in terms of welfare, GBT ranks first among single women but for the whole population the best policies are subsidies on low wages, unconditional transfers or a combination of the two.
Keywords: H2; I3; J2; 330; gender based taxation; wage subsidies; basic income; guaranteed minimum income; labour supply; social welfare